There Are Things with No Price: Non/Motherhood, Agency, and Identity in The Witcher - Stasiewicz-Bieńkowska, Agnieszka (Literatūra, 2025)
The Witcher (Wiedźmin) – a fantasy storyworld originating from Andrzej Sapkowski’s Polish literary series – is fundamentally shaped by narratives of reproduction, in/fertility, and non/motherhood, raising critical questions about women’s roles and empowerment. From fertility cults and enforced sterilization to genetic experimentation and dynastic ambitions, these themes drive character arcs and central conflicts across the saga’s transmedial universe. This article examines the interplay of non/motherhood, female agency, and bodily autonomy in Sapkowski’s books and the Netflix adaptation, exploring how The Witcher envisions women’s success and worth through the tensions between maternal and non-maternal identities. Grounded in fantasy, Gothic, and horror traditions, this analysis maps gynaehorror tropes in unwanted maternity and examines how the archetypes of absent and self-sacrificing mothers speak to the constraints on culturally legible identities of women. Finally, an adaptation studies approach highlights the ideological shifts across different media. While the franchise explicitly advocates reproductive freedom, its treatment of non-maternal desires reveals a paradox: reproductive rights are championed in principle, yet character arcs privilege idealized motherhood. The Netflix adaptation further narrows the non-maternal possibilities of the source material, reimagining originally non-maternal characters through maternal lens. Ultimately, the self-sacrificing mother emerges as the defining framework for female value, reflecting the franchise’s internal contradictions and broader cultural anxieties surrounding non/motherhood.
Keywords: The Witcher; motherhood; childlessness; adaptation; reproductive rights